2000
DOI: 10.1063/1.126562
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the formation of the 2.8 eV luminescence band in p-type GaN:Mg

Abstract: The stability of defects present in GaN:Mg has been investigated using photoluminescence (PL) spectroscopy. The two dominant defect-related PL emission bands in p-type GaN were investigated, the blue band at 2.8 eV and the ultraviolet (UV) emission band at 3.27 eV. The intensity of the 3.27 eV PL band increases with increasing resistivity, whereas the 2.8 eV PL band intensity increases with a decrease in resistivity. The luminescence data is explained by a model whereby the concentration of luminescent centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
79
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 11 publications
15
79
0
Order By: Relevance
“…For the shallow acceptor with an optical binding energy of around 225 meV, Mg Ga [8,9] is the most promising candidate. Whereas possible candidates for the shallow donor (20-30 meV) are O [10], Si [11], H [12] and V N -H [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the shallow acceptor with an optical binding energy of around 225 meV, Mg Ga [8,9] is the most promising candidate. Whereas possible candidates for the shallow donor (20-30 meV) are O [10], Si [11], H [12] and V N -H [13].…”
Section: Resultsmentioning
confidence: 99%
“…Si Ga and O N are believed to have a E threshold for the displacement of the Si (or O) atom of the same order of magnitude as that for Ga and therefore should not be affected by the electron beam [15]. Recently, H [12] and V N -H [13] were proposed to be the shallow donor level in MOVPE-grown Mg-doped GaN. However, isolated H is expected to be a deep donor showing a negative Ubehaviour [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shahedipour, et al, based on a study of the PL and the hole concentration dependence on the annealing temperature, concluded that a deep V N -H donor complex is responsible for the BL [93]. Suski, et al, have performed high-pressure experiments which indicate that the pressure dependence of the BL peak position is much smaller than that of the band-gap, and is thus unlikely to be associated with a CB or SD transition [94].…”
Section: Self-compensationmentioning
confidence: 99%
“…Different models have been proposed to explain the so-called blue luminescence of Mg-doped GaN. This emission has been often attributed to a DAP transition involving a deep level, but there has been no consensus as to whether the deep defect is a deep donor 18,19 or a deep acceptor. 16 The temperature redshift of the blue GaN:Mg band observed in this work agrees with the proposed DAP nature of the emission.…”
mentioning
confidence: 99%